FETOMATERNAL OUTCOME IN PREGNANCY WITH GESTATIONAL THROMBOCYTOPENIA - Dr. Aishwarya Meshram; Dr. Azmat Jahan Mantoo; Prof. Dr. Cimona Lyn Saldanha; Dr Umer Hamid (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
BACKGROUND : Thrombocytopenia is second most common hematological abnormality during pregnancy,  and is  found to complicate 7% to 8% of pregnancy in India. Thrombocytopenia in pregnancy may be an isolated findings or it may be associated with systemic disorders  like severe preeclampsia , HELLP syndrome(hemolysis, elevated liver enzymes, low platelets), or AFLP(acute fatty liver of pregnancy).OBJECTIVE : To study the cases of thrombocytopenia during pregnancy and its effect on feto-maternal outcome.MATERIAL AND METHODS: A prospective observational study was carried out in tertiary hospital, 422 pregnant women who attended the antenatal clinic regularly were enrolled ( >30 weeks of gestation). Out of 422 pregnant women, n=211 were women with normal platelet count were taken as control group and those with low count (